Greed For Power In William Shakespeare's King Lear Drama (1606) : A Psychoanalytic Approach - Citra R, Eka (2012)
The major problem of this study is how the greed for power is reflected in the major character's personality. The aim of this study is to analyze William Shakespeare's King Lear drama based on the structural elements and the development of personality of the major character based on Psychoanalytic Perspective. This study focuses on the major characters, namely Edmund, Goneril and Regan. The method of data collection is qualitative method. This study uses two data sources, namely primary and secondary data source. The primary data source is the script of the play itself, while the secondary data source includes books and other data that have relationship with the research. Technique of the Data Collection is taking note, while the technique of Data Analysis in this study is descriptive analysis. Based on the structural analysis it is evident that in this drama, William Shakespeare wants to deliver a message that greed for power can bring misfortune to ourselve and other people. Based on the psychological analysis, it is clear that in King Lear drama Shakespeare describes a psychological phenomenon, in which the major characters, Edmund, Goneril and Regan have some qualities as strong desire to get an ability and authority to control everything named greed for power.